Extracellular Vesicles as Natural Delivery Carriers Regulate Oxidative Stress Under Pathological Conditions - Qi, Hongzhao; Wang, Yingruo; Fa, Shunxin; Yuan, Changqing; Yang, Lijun (Frontiers in Bioengineering and Biotechnology, 2021)
Extracellular vesicles are cellular secretory particles that can be used as natural drug delivery carriers. They have successfully delivered drugs including chemotherapeutics, proteins, and genes to treat various diseases. Oxidative stress is an abnormal physiological phenomenon, and it is associated with nearly all diseases. In this short review, we summarize the regulation of EVs on oxidative stress. There are direct effects and indirect effects on the regulation of oxidative stress through EVs. On the one hand, they can deliver antioxidant substances or oxides to recipient cells, directly relieving or aggravating oxidative stress. On the other hand, regulate factors of oxidative stress-related signaling pathways can be delivered to recipient cells by the mediation of EVs, realizing the indirect regulation of oxidative stress. To the best of our knowledge, however, only endogenous drugs have been delivered by EVs to regulate oxidative stress till now. And the heterogeneity of EVs may complicate the regulation of oxidative stress. Therefore, this short review aims to draw more attention to the EVs-based regulation of oxidative stress, and we hope excellent EVs-based delivery carriers that can deliver exogenous drugs to regulate oxidative stress can be exploited.